2021
DOI: 10.1002/jsfa.11144
|View full text |Cite
|
Sign up to set email alerts
|

A mouse model of short‐term, diet‐induced fatty liver with abnormal cardiolipin remodeling via downregulated Tafazzin gene expression

Abstract: Background Cardiolipin (CL) helps maintain mitochondrial structure and function. Here we investigated whether a high carbohydrate diet (HCD) fed to mice for a short period (5 days) could modulate the CL level, including that of monolysoCL (MLCL) in the liver. Results Total CL in the HCD group was 22% lower than that in the normal chow diet (NCD) group (P < 0.05). The CL72:8 level strikingly decreased by 93% (P < 0.0001), whereas total nascent CLs (CLs other than CL72:8) increased (P < 0.01) in the HCD group. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…After 24 h, the cells were treated with PBS, 0.25 mM OA only, 0.25 mM OA plus 200 and 400 μM compound 2 , or 0.25 mM OA plus 200 and 400 μM compound 4 . After another 24 h, RNA extraction and complementary DNA synthesis were performed, according to the manufacturer’s instructions and a previous study [ 49 ]. The sequences of the primers used are shown in the Supplementary Materials, Table S1 : adipose triglyceride lipase ( ATGL ), diacylglycerol O-acyltransferase 1 ( DGAT1 ), sterol regulatory element-binding protein 1 ( SREBP1 ), fatty acid synthase ( FASN ), stearoyl-CoA desaturase 1 ( SCD1 ), and glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ).…”
Section: Methodsmentioning
confidence: 99%
“…After 24 h, the cells were treated with PBS, 0.25 mM OA only, 0.25 mM OA plus 200 and 400 μM compound 2 , or 0.25 mM OA plus 200 and 400 μM compound 4 . After another 24 h, RNA extraction and complementary DNA synthesis were performed, according to the manufacturer’s instructions and a previous study [ 49 ]. The sequences of the primers used are shown in the Supplementary Materials, Table S1 : adipose triglyceride lipase ( ATGL ), diacylglycerol O-acyltransferase 1 ( DGAT1 ), sterol regulatory element-binding protein 1 ( SREBP1 ), fatty acid synthase ( FASN ), stearoyl-CoA desaturase 1 ( SCD1 ), and glyceraldehyde-3-phosphate dehydrogenase ( GAPDH ).…”
Section: Methodsmentioning
confidence: 99%
“…CL is a lipid necessary for mitochondrial energy metabolism [ 8 ]. CL72:8, which contains four LA molecules, is the mature and functional form, and CL72:8 is the major component of hepatocytes in vivo [ 37 ]. In cultured C3A cells, the concentration of CL72:8 was only approximately 0.30% of the total concentration.…”
Section: Discussionmentioning
confidence: 99%
“…This partially suggests the cleavage of glucoside metabolites to form aglycone metabolites and the appearance of new metabolites, including 34. The GNPS molecular network generated the data of ion parent detected from the BE initial sample (in green color), BE derivatized sample (purple), and a combination of both extract samples, leading to the identification of 16 molecules (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50), including the unknown ion parent predicted to be β-carboline alkaloid 34 (Figure 3). The ion parents are represented by nodes in the molecular network (MN), with chemically related metabolites clustered together.…”
Section: Molecular Networking and Detection Of β-Carboline 34 In Modi...mentioning
confidence: 99%
“…The classical MN workflow using the GNPS platform was performed as described in Section 3.3.2.B. Metabolite dereplication revealed that 33 parent ions matched known metabolites (34)(35)(36)(37)(38)(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)(49)(50)(51) in the GNP library. The parent ions from liquid chromatography with tandem mass spectrometry (LC-MS/MS) analysis of the modified extracts were dereplicated as follows: β-carboline alkaloids compound (34), L -5-hydroxy-tryptophan (35), L -Kynurenine (36), hypnophilin (37), L-tryptophan (38), isocitrate| (39), 13a-Hydroxylupanin (40), MoNA:2488524 2 (41), ethylene Thiourea (42), N-Hydroxytetraadecanoylleucine (43), putrescine (44), 13-Docosenamide (45), 1-Hexadecanoyl-sn-glycerol (46), abrine (47), DL -Indole-3-lactic acid (48), MoNA:2488004 (49), and N-Acetylhistidine (50).…”
Section: Chemo-selective Derivatization Of Vanilla Bean Extracts Unde...mentioning
confidence: 99%
See 1 more Smart Citation